Efficacy of Vedolizumab in Patients with Antibiotic and Anti-tumor Necrosis Alpha Refractory Pouchitis. Issue 1 (January 2017) - Philpott, Jessica; Ashburn, Jean; Shen, Bo
Abstract : Article first published online 7 December 2016.